Analisis Proses Pembiayaan Bermasalah Produk Mudharabah Pada PT.Bank Syariah Indonesia KCP. Stabat - Khairin Dinda Putri; Muhammad Saleh; Diyan Yusri (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2022)
This research aims to analyze the problematic financing process of mudharabah products at PT. Bank Syariah Indonesia KCP. Stabat. The type of research used in this research is field research with a qualitative approach. The data used is primary data and secondary data. Data collection is carried out by interviews and documentation. Data analysis is carried out by data reduction, presentation of data (Display data), conclusion drawing and verification data. The results of the study showed that the financing procedure at PT. Bank Syariah Indonesia KCP Stabat can be said to be quite long and complicated. Problematic financing is always caused by the debtor's fault. But problematic financing that arises in a financial institution is based on 2 (two) factors, namely internal factors or factors from the financial institution itself that is less selective in providing a financing to its customers, while external factors that come from the customer / debtor itself, either intentionally or unintentionally in fulfilling its obligation to pay installments or the business carried out does not develop.